2015
DOI: 10.1371/journal.pone.0127300
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Stem Cell Markers in the Intestinal Metaplasia of Stomach and Barrett’s Esophagus

Abstract: Gastric intestinal metaplasia (IM) is a highly prevalent preneoplastic lesion; however, the molecular mechanisms regulating its development remain unclear. We have previously shown that a population of cells expressing the intestinal stem cell (ISC) marker LGR5 increases remarkably in IM. In this study, we further investigated the molecular characteristics of these LGR5 + cells in IM by examining the expression profile of several ISC markers. Notably, we found that ISC markers—including OLFM4 and EPHB2—are pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…As shown in Figure 3j, GMCs with expressing the OLFM4 were rarely detected in the CAG lesion (0.4%), while the number of them (remarkably) increase in the wild IM lesion (8%) and reach a peak in the severe IM lesion (26%). In the EGC lesion, the GMC disappeared and the proportion of OLFM4-expressing cells reach the peak, which have been confirmed by previous immunohistochemistry studies 36 . We further assessed the co-expression of MUC6 and OLFM4 within the GMCs in the IM lesion, and found that the expression of OLFM4 displayed a significant negative correlation with that of MUC6 (p = 0.003, Supplementary figure 10).…”
Section: Characterization Of the Single Cell Expression Profiles For supporting
confidence: 85%
“…As shown in Figure 3j, GMCs with expressing the OLFM4 were rarely detected in the CAG lesion (0.4%), while the number of them (remarkably) increase in the wild IM lesion (8%) and reach a peak in the severe IM lesion (26%). In the EGC lesion, the GMC disappeared and the proportion of OLFM4-expressing cells reach the peak, which have been confirmed by previous immunohistochemistry studies 36 . We further assessed the co-expression of MUC6 and OLFM4 within the GMCs in the IM lesion, and found that the expression of OLFM4 displayed a significant negative correlation with that of MUC6 (p = 0.003, Supplementary figure 10).…”
Section: Characterization Of the Single Cell Expression Profiles For supporting
confidence: 85%
“…Inflammation‐related factors, such as activator protein 1, NF‐κB, retinoic acid, and granulocyte colony‐stimulating factor, have been reported to regulate OLFM4 expression . In addition, recent studies have demonstrated that LGR5 increases OLFM4 expression through the Wnt signaling pathway and promotes stem cell property in the intestine . LGR5 is reported to be expressed in HCC; however, no reports have focused on the interaction between LGR5 and OLFM4.…”
Section: Discussionmentioning
confidence: 99%
“…(20,(42)(43)(44) In addition, recent studies have demonstrated that LGR5 increases OLFM4 expression through the Wnt signaling pathway and promotes stem cell property in the intestine. (27)(28)(29) LGR5 is reported to be expressed in HCC (45,46) ; however, no reports have focused on the interaction between LGR5 and OLFM4. Moreover, no previous studies have shown the effects of LGR5 or OLFM4 on cancer stem cell-like property in any malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations